2015
DOI: 10.1038/labinvest.2015.44
|View full text |Cite
|
Sign up to set email alerts
|

High-mobility group box 1 accelerates lipopolysaccharide-induced lung fibroblast proliferation in vitro: involvement of the NF-κB signaling pathway

Abstract: The mechanism underlying lipopolysaccharide (LPS)-induced aberrant proliferation of lung fibroblasts in Gram-negative bacilli-associated pulmonary fibrosis is unknown. High-mobility group box 1 (HMGB1) is a ubiquitous nuclear protein that is released from the nuclei of lung fibroblasts after LPS stimulation. It can exasperate LPS-induced inflammation and hasten cell proliferation. Thus, this study investigated the effects of LPS-and/or HMGB1-stimulating murine lung fibroblasts on gene expression using various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Lots of literatures reported that NF‐κB pathway was activated in pneumonia . Earlier research also confirmed that LPS could activate NF‐κB pathway in lung fibroblast cells . Shi et al indicated that silencing circANKRD36 could inhibit NF‐κB pathway in myocardial H9c2 cells .…”
Section: Discussionmentioning
confidence: 96%
“…Lots of literatures reported that NF‐κB pathway was activated in pneumonia . Earlier research also confirmed that LPS could activate NF‐κB pathway in lung fibroblast cells . Shi et al indicated that silencing circANKRD36 could inhibit NF‐κB pathway in myocardial H9c2 cells .…”
Section: Discussionmentioning
confidence: 96%
“…It has been reported that HMGB1 accelerates lipopolysaccharide-induced lung fibroblast proliferation in vitro via the NF-κB signaling pathway (38). Conversely, the present study demonstrated that NF-κB activation in lung fibroblasts, induced by HMGB1, may promote TGF-β1 release and induce fibroblast to myofibroblast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…We elected to use a combined insult because this model (a) Associates the effect of DAMPs and PAMPs on a mono‐cellular culture, better resembling the septic milieu to which TEC may be exposed; (b) Combines prototypical molecules that induce early (LPS) and late (HMGB1) inflammatory injury during sepsis; (c) Was shown by Li et al, to increase mRNA and protein expression of TLR2 and 4 receptors more than LPS or HMGB1 alone, which is known to be part of the innate renal response to sepsis; and (d) proved to increase MCP‐1 more than LPS alone (Figure S1), without inducing more cell death in our preliminary studies. Inflammatory mix was composed of the following concentrations based on our preliminary data (Figure S1) and work by Li et al 28 : lipopolysaccharide ( Escherichia coli , Sigma, L2630 in HBSS media, Gibco 14025‐076, 10 μg/mL) plus High mobility group box 1 (HMGB1) (1 μg/mL). We selected the concentrations of AICAR and Compound C based on preliminary pilot studies showing adequate AMPK activation and inhibition (data not shown).…”
Section: Methodsmentioning
confidence: 99%